1996
DOI: 10.1897/1551-5028(1996)015<1335:isopha>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Study of Precision: Hyalella Azteca and Chironomus Tentans Freshwater Sediment Toxicity Assays

Abstract: Abstract-Standard 10-d whole-sediment toxicity test methods have recently been developed by the U.S. Environmental Protection Agency (EPA) for the amphipod Hyalella azteca and the midge Chironomus tentans. An interlaboratory evaluation of method precision was performed using a group of seven to 10 laboratories, representing government, academia, and environmental consulting firms. The test methods followed the EPA protocols for 4-d water-only reference toxicant (KCl) testing (static exposure) and for 10-d whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 5 publications
1
24
0
5
Order By: Relevance
“…A second edition was published 6 years later, which described methods for evaluating survival after 28, 35 and 42 days, growth after 28 and 42 days, and reproduction during a 28-to 42-day period (USEPA, 2000). Burton et al (1996) reported and discussed in detail two ringtests organized by the US EPA in 1993 on the H. azteca assay, namely a 96-h test on a "water-only" reference chemical and a 10-day "whole-sediment" test, both of which involved 10 participants. In 1996/1997 the USEPA coordinated a second series of round-robin tests and reported the results of 10-day assays with survival as effect criterion, and of "long term" (28-day) tests based on survival and growth (USEPA, 2000).…”
Section: History Of the Hyalella Azteca Whole-sediment Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A second edition was published 6 years later, which described methods for evaluating survival after 28, 35 and 42 days, growth after 28 and 42 days, and reproduction during a 28-to 42-day period (USEPA, 2000). Burton et al (1996) reported and discussed in detail two ringtests organized by the US EPA in 1993 on the H. azteca assay, namely a 96-h test on a "water-only" reference chemical and a 10-day "whole-sediment" test, both of which involved 10 participants. In 1996/1997 the USEPA coordinated a second series of round-robin tests and reported the results of 10-day assays with survival as effect criterion, and of "long term" (28-day) tests based on survival and growth (USEPA, 2000).…”
Section: History Of the Hyalella Azteca Whole-sediment Testmentioning
confidence: 99%
“…The authors concluded that the case studies "demonstrated the robustness of the methods for successfully conducting toxicity tests with H. azteca". Burton et al (1996) gave a table on the inter-laboratory precision of the survival values for the 10-day H. azteca toxicity tests performed in 1993 by the USEPA (USEPA, 1994) with four sediments. The mean percentage survival was quite different in the four sediments, ranging from 3.3% to 94.5%.…”
Section: Test Procedures Precision and Sensitivity Of The Hyalella Amentioning
confidence: 99%
“…In addition, other potentially deformity‐inducing stress factors are yet to be laboratory tested. Factors such as larval density (Boglione et al ), developmental rates (Reimer et al ), dietary constituents (Cahu et al ), and pathogens (Johnson et al ) have demonstrated deformity‐inducing effects in other taxa, and are worth further consideration. Developmental rates may be of particular interest, given the faint effects suggested in our nutritional and developmental tests.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the interlaboratory elutriate tests demonstrated substantial agreement and similar sensitivity among both test species in the sediment samples tested. Burton et al (1996) have noted that all methods have inherent variability that must be taken into account when interpreting test results. The methods used in this study did not always find toxicity at the same sites, indicating that the elutriate preparations, storage times, and subsequent bioassay tests had built-in biases.…”
Section: Discussionmentioning
confidence: 99%